2009
DOI: 10.5194/bg-6-2313-2009
|View full text |Cite
|
Sign up to set email alerts
|

Physiological basis for high CO<sub>2</sub> tolerance in marine ectothermic animals: pre-adaptation through lifestyle and ontogeny?

Abstract: Abstract. Future ocean acidification has the potential to adversely affect many marine organisms. A growing body of evidence suggests that many species could suffer from reduced fertilization success, decreases in larval-and adult growth rates, reduced calcification rates, and even mortality when being exposed to near-future levels (year 2100 scenarios) of ocean acidification. Little research focus is currently placed on those organisms/taxa that might be less vulnerable to the anticipated changes in ocean che… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
430
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 586 publications
(447 citation statements)
references
References 145 publications
12
430
1
4
Order By: Relevance
“…117 On the other hand substantial acid-base regulatory abilities as found in most cephalopod species represents a common feature that was suggested to make ectothermic marine animals robust to seawater acidification. 45 However, metabolic data from the cuttlefish S. officinalis (acute exposure to 0.6 kPa pCO 2 ) and the squids Dosidicus gigas (acute exposure to 0.1 kPa pCO 2 ) and Sepiteuthis lessoniana (acute; 20 h medium term; 168 h 0.16 and 0.41 kPa pCO 2 ) indicated that these animals respond very differently toward environmental hypercapnia. 12,118,119 Although these studies partly used unrealistically high pCO 2 levels, in the context of environmental hypercania (usually >0.1 kPa), they could indicate a higher sensitivity in active pelagic squids compared to cuttlefish that have a benthic lifestyle.…”
Section: Role Of Ion Regulatory Epithelia During Acclimation To Envirmentioning
confidence: 99%
See 3 more Smart Citations
“…117 On the other hand substantial acid-base regulatory abilities as found in most cephalopod species represents a common feature that was suggested to make ectothermic marine animals robust to seawater acidification. 45 However, metabolic data from the cuttlefish S. officinalis (acute exposure to 0.6 kPa pCO 2 ) and the squids Dosidicus gigas (acute exposure to 0.1 kPa pCO 2 ) and Sepiteuthis lessoniana (acute; 20 h medium term; 168 h 0.16 and 0.41 kPa pCO 2 ) indicated that these animals respond very differently toward environmental hypercapnia. 12,118,119 Although these studies partly used unrealistically high pCO 2 levels, in the context of environmental hypercania (usually >0.1 kPa), they could indicate a higher sensitivity in active pelagic squids compared to cuttlefish that have a benthic lifestyle.…”
Section: Role Of Ion Regulatory Epithelia During Acclimation To Envirmentioning
confidence: 99%
“…45,48,117 Environmental hypercapnia that alters positive diffusion gradients of CO 2 from the animal to the seawater will affect the acid-base physiology of all water breathing animals as intra-and extra-cellular CO 2 concentrations will increase as well to maintain a sufficient diffusion gradient to excrete metabolic CO 2 . 45 Among a range of marine species, some have been identified as more sensitive (e.g. less active calcifying species such as corals or echinoderms) whereas others (many active species such as adult fish and cephalopods) can tolerate relatively high CO 2 concentrations over long exposure times.…”
Section: Role Of Ion Regulatory Epithelia During Acclimation To Envirmentioning
confidence: 99%
See 2 more Smart Citations
“…(Keul et al, 2013), and larvae of the Pacific oyster Crassostrea gigas (Gazeau et al, 2011) an inhibitor (Bach et al, 2011(Bach et al, , 2013(Bach et al, , 2015Jokiel, 2011aJokiel, , b, 2013Jokiel et al, 2014 (Bach et al, 2015). Indeed, HCO − 3 uptake is a common mechanism to buffer acidosis and might be facilitated at higher HCO − 3 availability (Boron, 2004;Melzner et al, 2009;Stumpp et al, 2012).…”
Section: Stabilitymentioning
confidence: 99%